Determination of Avermectins Residues in Soybean, Bean, and Maize Using a QuEChERS-Based Method and Ultra-High-Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry - Fernanda Uczay (MDPI AG, 2021)
Soybean, maize, and bean are crops of great economic importance, but in recent years have suffered with infestations of the caterpillar Helicoverpa armigera, with the main reason being the resistance of this pest to most pesticides. Avermectin emamectin benzoate was recently released to control this pest. Other avermectins, like abamectin, doramectin, eprinomectin, and ivermectin are used in large scale because they potent acaricidal, anthelmintic, and insecticidal activities. Thus, a simple and fast method for the determination of avermectins in these crops based on a quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction procedure and ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS) analysis was developed and validated. For extraction, water followed by acetonitrile:isopropanol and a partition step with salts was stablished. With the clean-up step using activated EMR-Lipid, limits of detection of 1.2 μg kg−1 for abamectin, doramectin, emamectin benzoate, and ivermectin, and of 2.4 μg kg−1 for eprinomectin were achieved. The validation showed satisfactory results and the method was successfully applied to commercial samples, indicating that it is suitable for routine analysis.